Optimization of Friction Stir Welding Process Parameters to joint 7075-T6 Aluminium Alloy by Utilizing Taguchi Technique (Journal of Engineering, 2019)
In this study, a 3 mm thickness 7075-T6 aluminium alloy sheet was used in the friction stir welding process. Using the design of experiment to reduce the number of experiments and to obtain the optimum friction stir welding parameters by utilizing Taguchi technique based on the ultimate tensile test results. Orthogonal array of L9 (33) was used based on three numbers of the parameters and three levels for each parameter, where shoulder-workpiece interference depth (0.20, 0.25, and 0.3) mm, pin geometry (cylindrical thread flat end, cylindrical thread with 3 flat round end, cylindrical thread round end), and thread pitch (0.8, 1, and 1.2) mm) this technique executed by Minitab 17 software. The results showed that the optimum friction stir welding parameters were 0.25 mm shoulder-workpiece interference depth, cylindrical thread flat end pin shape, 1.2 mm thread pitch depending on the S ̸ N ratio and ANOVA analysis and the welding efficiency was 93.3% based on the ultimate tensile stress.